2017
DOI: 10.1016/j.jacc.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Complexity and Outcomes of Extended Dual Antiplatelet Therapy After Percutaneous Coronary Intervention

Abstract: Complex target-lesion anatomy is associated with increased ischemic events, particularly within the first year after PCI. Among those without events in the first 12 months, the benefits of extending DAPT were similar in subjects with and without complex lesions. A high DAPT score identified those experiencing the most benefit from extended treatment among patients with and without complex anatomy. (The Dual Antiplatelet Therapy Study [DAPT Study]; NCT00977938).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 13 publications
6
75
1
Order By: Relevance
“…In an individual patient pooled meta-analysis consisting of studies comparing 3–6 months DAPT with 12–24 months DAPT, 12–24 months DAPT was associated with significant reductions in MACE compared with 3–6 months DAPT [38]. Conversely, in the DAPT study among patients without events in the first 12 months, the benefits of extending DAPT beyond one year were similar in subjects with and without complex lesions [39]. These findings suggest that complex PCI may be a more useful discriminator for predicting the benefit of DAPT within the first year after PCI, but less useful for predicting benefit of longer durations after 12 months.…”
Section: Available Evidencementioning
confidence: 99%
“…In an individual patient pooled meta-analysis consisting of studies comparing 3–6 months DAPT with 12–24 months DAPT, 12–24 months DAPT was associated with significant reductions in MACE compared with 3–6 months DAPT [38]. Conversely, in the DAPT study among patients without events in the first 12 months, the benefits of extending DAPT beyond one year were similar in subjects with and without complex lesions [39]. These findings suggest that complex PCI may be a more useful discriminator for predicting the benefit of DAPT within the first year after PCI, but less useful for predicting benefit of longer durations after 12 months.…”
Section: Available Evidencementioning
confidence: 99%
“…However, restenosis or ST in the LM lesion could result in serious consequences and may post LM‐PCI patients could benefit from extended duration of dual antiplatelet therapy. Dual antiplatelet therapy beyond 1 year reduced major adverse events without increased bleeding events in complex lesion PCI compared to 1‐year duration of dual antiplatelet therapy . Risk models are available to determine the duration of dual antiplatelet therapy and obtain the maximum net clinical benefit but do not contain information whether patients post LM‐PCI should be on longer duration of therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy beyond 1 year reduced major adverse events without increased bleeding events in complex lesion PCI compared to 1-year duration of dual antiplatelet therapy. 40,41 Risk models are available to determine the duration of dual antiplatelet therapy and obtain the maximum net clinical benefit but do not contain information whether patients post LM-PCI should be on longer duration of therapy. 42,43 Further studies are required to elucidate the optimal stenting technique in LM-PCI and duration of antiplatelet therapy.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The study found that a longer DAPT duration significantly increased TIMI major and minor bleeding in patients with higher scores but not in those with lower risk scores ( p interaction = 0.007). Similarly, a scoring system was developed by Yeh et al and used to analyze extended DAPT use of 30 months versus 12 months in patients with complex lesions such including ULM, length >30 mm, and bypass grafts. In the 25 416 patients enrolled, complex target lesions had higher rates of MI/ST in the first 12 months after PCI (3.9% vs 2.4%; P < 0.001).…”
Section: Dual Antithrombotic Therapy After Pcimentioning
confidence: 99%
“…83 The study found that a longer DAPT duration significantly increased TIMI major and minor bleeding in patients with higher scores but not in those with lower risk scores (p interaction = 0.007). Similarly, a scoring system was developed by Yeh et al 84…”
Section: Dual Antithrombotic Therapy After Pcimentioning
confidence: 99%